2007
DOI: 10.1073/pnas.0703933104
|View full text |Cite
|
Sign up to set email alerts
|

A variant of mitochondrial protein LOC387715/ARMS2, not HTRA1, is strongly associated with age-related macular degeneration

Abstract: Genetic variants at chromosomes 1q31-32 and 10q26 are strongly associated with susceptibility to age-related macular degeneration (AMD), a common blinding disease of the elderly. We demonstrate, by evaluating 45 tag SNPs spanning HTRA1, PLEKHA1, and predicted gene LOC387715/ARMS2, that rs10490924 SNP alone, or a variant in strong linkage disequilibrium, can explain the bulk of association between the 10q26 chromosomal region and AMD. A previously suggested causal SNP, rs11200638, and other examined SNPs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
320
3
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(348 citation statements)
references
References 46 publications
(75 reference statements)
15
320
3
6
Order By: Relevance
“…Instead, the profile reproduced observations drawn from the C57BL/6J mouse model wherein there was a correlation between the higher G2 levels and the presence of AMD (OR = 5.8, 95% confidence interval 0.98-34.4) even though prostaglandin G2 levels did not differ between the AMD and control groups. The importance of the Ala 69 →Ser change in ARMS2 mutation in predicting the incidence of AMD was previously described (32). Our finding that addition of this second parameter did not improve our model is not surprising.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Instead, the profile reproduced observations drawn from the C57BL/6J mouse model wherein there was a correlation between the higher G2 levels and the presence of AMD (OR = 5.8, 95% confidence interval 0.98-34.4) even though prostaglandin G2 levels did not differ between the AMD and control groups. The importance of the Ala 69 →Ser change in ARMS2 mutation in predicting the incidence of AMD was previously described (32). Our finding that addition of this second parameter did not improve our model is not surprising.…”
Section: Discussionsupporting
confidence: 59%
“…First, we performed a genetic screen for the Ala 69 →Ser change (G→T mutation) in the ARMS2 gene, which is implicated in development of AMD (32). Mass spectrometry analysis of serum lipids indicated that DHA levels in the AMD samples were decreased as compared with those in the non-AMD control group (Fig.…”
Section: General Characterization Of Human Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The high level of LD has made it difficult to determine which of these genes is primarily responsible for the increased risk of AMD (attributable to this region of chromosome 10q26). However, a recent report suggests that a single SNP (rs10490924), which changes the coding sequence of ARMS2, may account for the association between chromosome 10q26 and increased risk for AMD (Kanda et al, 2007). Although the precise role of ARMS2 in AMD disease aetiology has yet to be elucidated, its role in mitochondrial function is thought to be important (Rivera et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Common single nucleotide polymorphisms (SNPs) in the complement factor H (CFH) gene on chromosome 1, [7][8][9][10] and in two loci on chromosome 10q26, that is, ARMS2 (formerly labelled as LOC387715) [11][12][13][14][15] and the HtrA serinepeptidase 1 (HtrA1) gene [16][17][18][19] showed strong associations with the risk of advanced AMD. These results have been extensively replicated in studies conducted in various populations and settings (for an overview, see Jakobsdottir et al 20 ).…”
Section: Introductionmentioning
confidence: 99%